2023
DOI: 10.1002/adbi.202300271
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chemotherapeutic Stress Depends on The Nature of Breast Cancer Spheroid and Induce Behavioral Plasticity to Resistant Population

Sukanya Gayan,
Abhishek Teli,
Akshay Sonawane
et al.

Abstract: Cellular or tumor dormancy, identified recently as one of the main reasons behind post‐therapy recurrence, can be caused by diverse reasons. Chemotherapy has recently been recognized as one of such reasons. However, in‐depth studies of chemotherapy‐induced dormancy are lacking due to the absence of an in vitro human‐relevant model tailor‐made for such a scenario. This report utilized multicellular breast cancer spheroid to create a primary platform for establishing a chemotherapy‐induced dormancy model. It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 94 publications
0
1
0
Order By: Relevance
“…Simultaneously, dormant cells can re-enter the cell cycle, exhibiting drug resistance and heightened malignancy. Through dormancy, cancer cells gain increased survival capabilities to resist adverse external factors [37,38]. In our study, we demonstrated that mitophagy is associated with the transition of HNSCC into a low-metabolism, low-proliferation dormant state during DDP treatment, endowing the tumor with enhanced drug resistance and CSC characteristics.…”
Section: Discussionmentioning
confidence: 56%
“…Simultaneously, dormant cells can re-enter the cell cycle, exhibiting drug resistance and heightened malignancy. Through dormancy, cancer cells gain increased survival capabilities to resist adverse external factors [37,38]. In our study, we demonstrated that mitophagy is associated with the transition of HNSCC into a low-metabolism, low-proliferation dormant state during DDP treatment, endowing the tumor with enhanced drug resistance and CSC characteristics.…”
Section: Discussionmentioning
confidence: 56%